2018
DOI: 10.1021/acs.joc.8b00649
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Symmetric and Unsymmetric Secondary Amines from the Ligand-Promoted Ruthenium-Catalyzed Deaminative Coupling Reaction of Primary Amines

Abstract: The catalytic system generated in-situ from the tetranuclear Ru–H complex with a catechol ligand (1/L1) was found to be effective for the direct deaminative coupling of two primary amines to form secondary amines. The catalyst 1/L1 was highly chemoselective for promoting the coupling of two different primary amines to afford unsymmetric secondary amines. The analogous coupling of aniline with primary amines formed aryl-substituted secondary amines. The treatment of aniline-d7 with 4-methoxybenzylamine led to t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
20
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 118 publications
1
20
0
Order By: Relevance
“…We previously reported that a phenol-coordinated cationic ruthenium–hydride complex is a highly effective catalyst for mediating the hydrogenolysis of aldehydes and ketones to give the corresponding aliphatic products . We subsequently devised a catalytic system generated in situ from a tetranuclear ruthenium–hydride complex and a catechol ligand to promote a direct deaminative coupling of primary amines . We have been exploring the coupling reactions of amines to further extend the synthetic utility of ligand-promoted catalysis, and herein, we disclose an efficient catalytic synthesis of quinazoline and quinazolinone derivatives from the dehydrogenative and deaminative coupling reactions of amino ketones and aminobenzamides with amines. …”
mentioning
confidence: 70%
See 1 more Smart Citation
“…We previously reported that a phenol-coordinated cationic ruthenium–hydride complex is a highly effective catalyst for mediating the hydrogenolysis of aldehydes and ketones to give the corresponding aliphatic products . We subsequently devised a catalytic system generated in situ from a tetranuclear ruthenium–hydride complex and a catechol ligand to promote a direct deaminative coupling of primary amines . We have been exploring the coupling reactions of amines to further extend the synthetic utility of ligand-promoted catalysis, and herein, we disclose an efficient catalytic synthesis of quinazoline and quinazolinone derivatives from the dehydrogenative and deaminative coupling reactions of amino ketones and aminobenzamides with amines. …”
mentioning
confidence: 70%
“…Adopting the previously developed deaminative coupling protocol, (17) we next sought the catalytic coupling reaction of the arylamides with amine substrates to form quinazolinone products. Thus, the treatment of 2aminobenzamide (0.5 mmol) with benzylamine (0.7 mmol) in dioxane (2 mL) at 140 °C in the presence of the catalyst system 1 (3 mol %)/L1 (10 mol %) led to the selective formation of the quinazolinone product 3a, which was analyzed by both GC and NMR spectroscopic methods (eq 2).…”
mentioning
confidence: 99%
“…The formation of secondary amines in the first place proceeds via two different pathways (Figure 2), both following the borrowing hydrogen mechanism. [6][7][8][9] The first way (alcohol amination, Figure 2, A) also starts with the dehydration (I) of the alcohol to the carbonyl compound. However, in the second step, instead of ammonia, the primary amine reacts in the condensation with the aldehyde or ketone (II), forming a secondary enamine and water.…”
Section: Introductionmentioning
confidence: 99%
“…Intermolecular self-condensation of primary amines (RNH 2 ) is one of the most efficient methods for the synthesis of symmetric secondary amines (R 2 NH, Scheme a). The beauty of this clean reaction scheme is illustrated by the highly atom-economical and selective production of the target secondary amine and the coproduction of ammonia as the only byproduct. The self-condensation process is free from the problem of organic waste formation involved in the conventional N,N-dialkylation of primary carboxamides or sulfonamides followed by cleavage of the amide moieties .…”
mentioning
confidence: 99%
“…The self-condensation of primary amines could be effectively catalyzed by both molecular and heterogeneous catalysts. Ru and Ir complexes have frequently been used to achieve the self-condensation of amines at 150–185 °C, affording the desired products in moderate to good yields. , A cobalt complex catalyzes this reaction at 120 °C . Heterogeneous catalysts such as Raney Ni, Pt–Sn/γ-Al 2 O 3 , Cu/Al 2 O 3 , NiCuFeO x , and Pd 3 Pb/Al 2 O 3 effectively promote this transformation at 120–145 °C .…”
mentioning
confidence: 99%